Midwifery-led care: A single mixed-methods synthesis. (2nd January 2023) - Kuipers, Yvonne; Degraeve, Julie; Bosmans, Valerie; Thaels, Ellen; Mestdagh, Eveline
ABSTRACT: Background: Midwifery Led Care (MLC) has shown to be beneficial for women and for midwives. The implementation of MLC remains challenging. Objective: To explore the utility of MLC and midwives' behavioural determinants. Methods: A systematic mixed-methods review was conducted, integrating data derived from methodologically different studies into a single mixed-methods synthesis. Data were organized using the Feasibility–Appropriateness–Meaningfulness–Effectiveness (FAME) scale. Behavioural MLC determinants were grouped in an extended Attitude–Social influence–Self-efficacy (ASE) model. After a synthesis and summary of the data and a descriptive thematic analysis, all FAME/ASE variables were quantified for a Bayesian Pearson correlation analysis. Results: The relationships between the FAME scales and ASE themes showed very strong evidence (BF 31.1–41.6), strong (BF 11.2–28.5) and to a lesser degree moderate (BF 3.1–9.7), and anecdotal evidence (BF 1.5–2.9). MLC utility was predominantly explained by the appropriateness and effectiveness of MLC and their correlations with the midwife's attitude, the perceived social influence of the public, supportive factors, regulation, professional and personal norms, and intention. Conclusion: To implement, scale up, and maintain MLC, a multipronged approach is needed. Midwives need to stand up for their professional identity in the wider culture and climate of maternity services to push the change for MLC.